Effect of Crystallographic Orientation on the Corrosion of Magnesium: Comparison of Film Forming and Bare Crystal Facets using Electrochemical Impedance and Raman Spectroscopy. (10th February 2017) - Bland, Leslie G.; Gusieva, K.; Scully, J.R.
Abstract: The corrosion rate of Mg indicates a strong crystallographic dependence in chloride-containing, alkaline environments that correlates inversely with oxide film thickness. In contrast, a different crystallographic orientation dependency is observed initially during open circuit corrosion in non-chloride containing, near neutral pH buffered, chelating environments such as Tris(hydroxymethyl)aminomethane (TRIS) and Ethylenediaminetetraacetic (EDTA) which minimize air-formed MgO oxides. The origins of the differences in the rates of the coupled corrosion processes as a function of crystallographic orientation were investigated utilizing electrochemical impedance spectroscopy (EIS) and Raman vibrational spectroscopy. High frequency constant phase elements (CPEs) were exploited to determine oxide thicknesses as a function of crystal orientation. In unbuffered NaCl, open circuit corrosion was faster on basal planes while lower corrosion rates were observed on low index, prismatic and pyramidal planes. This variation in rate with crystallographic orientation in 0.6 M NaCl was interpreted to depend on the MgO and Mg(OH)2 film thicknesses as a function of orientation. In particular, crystal planes with a lower MgO/Mg(OH)2 thickness corroded at higher rates as assessed in-situ by EIS and suggested by Raman spectroscopy. The crystallographic orientation dependence of corrosion seen initially upon exposure in the buffered neutral pH environments corresponded with crystal facet surface energy for bare Mg but this trend disappeared with exposure time and Mg(OH)2 films were then detected.